Challenges and Coping Strategies in Online Learning Among State University Students in South Central Mindanao, Philippines - Cris John Bryan C. Dela Cruz; Jericho L. Nueva; Aiza A. Pigkaulan; Carmina B. Rosal (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
The globe was altered by the pandemic, and the educational system saw change as well. The study found out how much difficulty State University students in South Central Mindanao, the Philippines, faced and what coping mechanisms they used when learning online. A non-experimental research design employing the descriptive- correlational technique was utilized. Weighted Mean, Pearson Product-Moment Correlation, and Analysis of Variance were used in the data analysis.  Results revealed that the level of challenges encountered by state university students in online learning indicated by adaptability struggle, connectivity issue, financial struggle is very high, while the coping strategies of the students indicated by time management, social support seeking, and self-regulation is high. There is a significant relationship between the challenges and coping strategies of state university students. There is a significant difference in the challenges and coping strategies of state university students when analyzed according to year level. Programs to help students develop self-regulation, social support seeking behavior, and time management may be implemented by the state university to help students cope with the challenges of online learning.